Hollow fiber nanofiltration membranes: A comparative review of interfacial polymerization and phase inversion fabrication methods. Issue 13 (2nd September 2017) - Urper, Gulsum Melike; Sengur-Tasdemir, Reyhan; Turken, Turker; Ates Genceli, Esra; Tarabara, Volodymyr V.; Koyuncu, Ismail
ABSTRACT: Membrane-based separation is now established as one of staple technologies used in water treatment and reuse applications. Nanofiltration, in particular, can be a cost-effective solution for removing large ions and low-molecular-weight compounds from water. Nanofiltration membranes have been manufactured mostly as flat sheets and used in spiral wound modules. Hollow fiber geometry, however, offers several advantages over flat sheet and other configurations. This paper overviews recent developments in the design of hollow fiber nanofiltration membranes and provides a comparative analysis of two main methods of their fabrication: interfacial polymerization and phase inversion.